NETO2 Is Deregulated in Breast, Prostate, and Colorectal Cancer and Participates in Cellular Signaling - Fedorova, Maria S.; Snezhkina, Anastasiya V.; Lipatova, Anastasiya V.; Pavlov, Vladislav S.; Kobelyatskaya, Anastasiya A.; Guvatova, Zulfiya G.; Pudova, Elena A.; Savvateeva, Maria V.; Ishina, Irina A.; Demidova, Tatiana B.; Volchenko, Nadezhda N.; Trofimov, Dmitry Y.; et al. (Frontiers in Genetics, 2020)
The NETO2 gene (neuropilin and tolloid-like 2) encodes a protein that acts as an accessory subunit of kainate receptors and is predominantly expressed in the brain. Upregulation of NETO2 has been observed in several tumors; however, its role in tumorigenesis remains unclear. In this study, we investigated NETO2 expression in breast, prostate, and colorectal cancer using quantitative PCR (qPCR), as well as the effect of shRNA-mediated NETO2 silencing on transcriptome changes in colorectal cancer cells. In the investigated tumors, we observed both increased and decreased NETO2 mRNA levels, presenting no correlation with the main clinicopathological characteristics. In HCT116 cells, NETO2 knockdown resulted in the differential expression of 17 genes and 2 long non-coding RNAs (lncRNAs), and was associated with the upregulation of circadian rhythm and downregulation of several cancer-associated pathways, including Wnt, transforming growth factor (TGF)-β, Janus kinase (JAK)-signal transducer and activator of transcription (STAT), mitogen-activated protein kinase (MAPK), and phosphatidylinositol 3-kinase (PI3K)/protein kinase B (AKT) pathways. Furthermore, we demonstrated the possibility to utilize a novel model organism, short-lived fish Nothobranchius furzeri, for evaluating NETO2 functions. Collectively, our findings demonstrate the deregulation of NETO2 in the breast, prostate, and colorectal cancer and its participation in the tumor development primarily through cellular signaling.